BMP4 Moderates Glycolysis and Regulates Activation and Interferon-Gamma Production in CD4+ T Cells - Huang, Feng; Hu, Lei; Zhang, Yuanmin; Qu, Xingmin; Xu, Junji (Frontiers in Immunology, 2021)
BMP4 is a key growth factor well known in promoting bone regeneration and has been reported to be able to regulate T cell development in the thymus. Here, we showed that BMP4 downregulates the activation of naïve CD4+ T cells and the IFN-γ production of CD4+ T cells without increasing regulatory T cells. BMP4 could also moderate glycolysis of T cells via regulating Hif1α expression. Furthermore, BMP4 showed a suppressive function on the IFN-γ production of CD4+ T cells in vivo. These findings reveal a mechanism by which BMP4 regulates activation and IFN-γ production in CD4+ T cells via metabolism moderation and suggests that BMP4 may be a potential therapeutic supplement in autoinflammatory diseases.